Iron Intake and Iron Inhibitor and Enhancer Intake with the Incidence of Anemia Among Adolescent Girls - Haniyyah Prastia Putri; A'immatul Fauziyah (Sarana Ilmu Indonesia (salnesia), 2023)
Anemia, especially iron deficiency anemia was marked with low hemoglobin (Hb) concentration than normal standard.Adolescents, especially girls when reached the age of menstruation were prone to this type of anemia because of blood loss from their monthly cycle. This research objective was to analyze the participant’s intake of iron, iron enhancers, and inhibitors intake and analyze its relationship to anemia incidence of MTs. Fadlurrahman, Bekasi 2022. This cross-sectional research used stratified random sampling based on their level of class. The participant’s number were 49 adolescent girls who met the inclusion and exclusion criteria. 36,70% of all subjects had anemia. Most subjects (75,51%) had low iron consumption, rare iron enhancers consumption (75,51%), and frequent inhibitors consumption (51,02%). All the independent variables (iron intake, iron enhancers consumption, and iron inhibitor consumption) had a significant relationship (p<0,05) to the dependent variable (anemia incidence). This finding implicated adolescent girls in MTs. Fadlurrahman needs to consume more iron-rich foods and their enhancers while lower its inhibitor intake.